Diagnosa Penyakit Hisprung pada Bayi menggunakan Metode Dempster Shafer - Nadia Nurhafiza; Rusmin Saragih; Melda Pita Uli Sitompul (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
Hirschsprung’s disease is a congenital disorder caused by abnormal nerve cell development in the large intestine, leading to chronic intestinal obstruction in infants. This condition often manifests through symptoms such as constipation, abdominal distension, vomiting, and failure to thrive. The weak immune system of infants makes them highly susceptible to bacterial infections and further complications. At Bidadari General Hospital, there were 110 patients suspected of having Hirschsprung’s disease. One of the major challenges in managing these cases is the limited number of medical specialists, particularly pediatricians and pediatric surgeons, resulting in long waiting times for accurate diagnosis, especially during peak service hours. To address this issue, this study applies the Dempster-Shafer method in an expert system to assist in diagnosing Hirschsprung’s disease based on clinical symptoms. The method effectively handles uncertainty and combines multiple pieces of medical evidence to produce more accurate diagnostic probabilities. The analysis results show that from the selected symptoms, the highest diagnosis probability corresponds to short-segment Hirschsprung’s disease with a confidence level of 71.54%. These findings suggest that the Dempster-Shafer method can serve as an effective alternative tool to support early and accurate diagnosis of Hirschsprung’s disease in infants.